PENGARUH OPTIMISME TERHADAP STRES AKADEMIK PADA SISWA SMAN 1 POLEWALI - Nur Fitriauliah Ilham, Lukman (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
Academic stress is a problem often experienced by students which can affect students' academic success. One of the factors that influences academic stress is optimism. Optimism makes students believe in their abilities to overcome academic stress. This research aims to determine the effect of optimism on students' academic stress. The method used was a quantitative approach with a sample size of 200 students from 7 classes of XII SMAN 1 Polewali. The data research method uses questionnaires and documentation. All instruments have met the validity test requirements using product moment correlation and reliability using Cronbach's alpha. This research uses an academic stress scale with a reliability of 0.845 and an optimism scale with a reliability of 0.733. Data analysis uses simple parametric regression analysis techniques. Data analysis produced a p value (0.932) > 0.05, which means there is no influence between optimism (X) on academic stress (Y). The unproven hypothesis in this study was caused bay cultural difference where academic stress can be influenced by family experience, high expectations from the family, socio-economic condition, area of residence (city or village), education, gender, and motivation.